Inflammation and autophagy in peripheral nerves of rodent models with metabolic syndrome and type 2 diabetes mellitus - Petra Baum; Thomas Ebert; Nora Klöting; Sontje Krupka; Matthias König; Sabine Paeschke; Peggy Stock; Michal Bulc; Matthias Blüher; Katarzyna Palus; Marcin Nowicki; Joanna Kosacka (Neuroscience Research)
Metabolic syndrome (MetS) and type 2 diabetes mellitus (T2D) are associated with inflammation and the accumulation of macrophages in peripheral nerves, which increases the risk of developing peripheral neuropathy (PN). We have previously investigated that macrophage infiltration in the peripheral nerves of animals with T2D (leptin-deficient ob/ob mice, leptin receptor-deficient db/db) correlated with PN, whereas this process in animals with MetS (Wistar Ottawa Karlsburg W (RT1u) WOKW rat) did not lead to neuropathic changes. Additional data presented in this study suggest an association between increased mRNA expression of the anti-inflammatory marker IL-10 and autophagy in the prevention of neuropathy.